Microsatellite based polymorphism and genetic diversity among Indian buffalo breeds - KANNUR, BHEEMASHANKAR H; FAIROZE, MD. NADEEM; GIRISH, P S; RENUKAPRASAD, C; KARABASANAVAR, NAGAPPA; BAGALE, SHAILESH; RUDRESH, B H (The Indian Journal of Animal Sciences, 2017)
Autosomal microsatellite markers allow estimation of expected heterozygosity and allele frequencies which may reveal the effects of genetic isolation, inbreeding, introgression and subdivision within livestock breeds. In the present study, 7 buffalo breeds (Bhadawari, Jaffrabadi, Murrah, Mehsana, Nagpuri, Pandharpuri and Surti) were studied using a panel of eight microsatellite markers selected based on polymorphic information content (PIC) for buffalo (Bubalus bubalis) species as per the guidelines of Food and Agricultural Organization. Frequency of breedspecific alleles was found lower in all the breeds studied; 4 out of 49 alleles showed a frequency of 8% while only one allele showed >10% frequency. In the present study, highest genetic distance was observed between Murrah and Surti (0.896) indicating their isolated breeding over several generations.